2012
DOI: 10.4236/ce.2012.326116
|View full text |Cite
|
Sign up to set email alerts
|

Student-Centered Learning Objects to Support the Self-Regulated Learning of Computer Science

Abstract: The most current computing curriculum guidelines focus on designing learning materials to prepare students for lifelong learning. Under the lifelong learning paradigm, students are responsible for controlling and monitoring their learning processes. This undoubtedly includes the ability to choose suitable learning materials. Correspondingly, instructional paradigms are shifting from teacher-centered to more student-centered models that require students to be self-regulated learners. On the other hand, recent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Despite this, by encouraging students' self-questioning and re-reading, DSLab feedback helped them be aware of SRL and metacognitive strategy use which, in turn, allowed them to achieve more efficient code. This finding is consistent with research which showed that students face difficulties in computer science education when they are not aware of SRL and metacognitive strategy use, so fostering them is important (Alharbi et al, 2012), whereas the use of feedback can be effective in supporting self-monitoring while performing problem-solving tasks (El Saadawi et al, 2010;Kramarski & Gutman, 2006;Lai et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite this, by encouraging students' self-questioning and re-reading, DSLab feedback helped them be aware of SRL and metacognitive strategy use which, in turn, allowed them to achieve more efficient code. This finding is consistent with research which showed that students face difficulties in computer science education when they are not aware of SRL and metacognitive strategy use, so fostering them is important (Alharbi et al, 2012), whereas the use of feedback can be effective in supporting self-monitoring while performing problem-solving tasks (El Saadawi et al, 2010;Kramarski & Gutman, 2006;Lai et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Though a variety of automated assessment tools has been developed over the years to assess programming assignments (Pettit et al, 2015), there is hardly any study that has investigated how an automated assessment tool for distributed programming could facilitate students' SRL strategies. Some studies in computer science education showed that students face difficulties when they are not aware of SRL and metacognitive strategy use; instead, when they employ SRL and metacognitive strategies they achieve good performance (Alharbi et al, 2012;Alhazbi & Hassan, 2013;Bergin et al, 2005).…”
mentioning
confidence: 99%
“…From above it seems that research should explore the potential of designing effective interventions that encourage the use of SRL strategies through technology-enhanced learning environments (TELEs) (Alharbi et al, 2012). The design and implementation of TELEs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there is limited literature on this topic in CS education. Alharbi, Henskens, & Hannaford (2012) reported typical CS students are visual, sensing, reflective, and sequential learners, suggesting that they learn best when exposed to visual representation and facts sequentially. CS students may also prefer to solve problems sequentially and to develop a visual interpretation of the problem.…”
Section: Self-regulation In Computer Programmingmentioning
confidence: 99%